THREE-DIMENSIONAL MOTION OF THE RADIAL ARTERY AND THE SPATIALITY, RHYTHMICITY, FORMABILITY AND INTENSITY OF TCM PULSE DIAGNOSIS - Niu, Xin; Yang, Xuezhi; Fu, Congyuan (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Traditional Chinese medicine (TCM) pulse diagnosis can reflect the condition of human bodies. 44 young healthy human beings were involved in the investigation of the relationship between the three dimensional motion of the radial artery and the spatiality, rhythmicity, formability and intensity of TCM pulse diagnosis in TCM pulse diagnostics. The color Doppler vascular imaging, the self-designed cardioelectric phasic marking and non-pressure arm bath-tube were used in the study. Both the radial artery and other arm superficial arteries had three forms of motion, namely diametrical motion, axial motion and the displacement of the axial center. The three forms of motion changed periodically, which was identical with that found in pulsation. The displacement of the vascular axial center was a three-dimensional message of the overall vascular revolving motion observed on a two-e level. Systematically studying the rules of vascular motion and the relationship between the rules of vascular motion and the spatiality, rhythmicity, formability and intensity of TCM pulse patterns has great significance in revealing the specificity of the vascular motion and explaining the mechanisms in the formation of TCM pulse diagnosis. This research could make TCM pulse diagnosis more understandable.